2000
DOI: 10.1024/0301-1526.29.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Das Ganglion des Hüftgelenkes als Differentialdiagnose eines pulsierenden Leistentumors

Abstract: Ganglion cysts of the hip joint are uncommon synovial-lined fluid-filled juxtaarticular groin lesions. Whereas in the past the correct diagnosis was often made only at surgery there are now valuable imaging methods used for the diagnostic work-up. In experienced hands ultrasonography (US) combined with colour duplex Doppler ultrasonography (CDDS) as a real-time imaging technique easily performed at the patient's bedside is a valid alternative to more expensive or invasive investigations. We report on a patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Inguinal swelling has been reported as another rare presentation of a hip ganglion [9]. Cassina et al reported a case of a hip ganglion presenting as a pulsatile groin mass [10]. Here, an aneurysm of the femoral artery was first suspected on conventional ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inguinal swelling has been reported as another rare presentation of a hip ganglion [9]. Cassina et al reported a case of a hip ganglion presenting as a pulsatile groin mass [10]. Here, an aneurysm of the femoral artery was first suspected on conventional ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound and colour Doppler ultrasonography are of great importance for diagnosing palpable and non-palpable cystic and soft tissue masses [10]; however, in our patient, the ultrasound was used only to establish the non-vascular nature of the cyst with the diagnosis first established using MRI.…”
Section: Discussionmentioning
confidence: 99%